If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.5(x-3)=3x-2.5
We move all terms to the left:
0.5(x-3)-(3x-2.5)=0
We multiply parentheses
0.5x-(3x-2.5)-1.5=0
We get rid of parentheses
0.5x-3x+2.5-1.5=0
We add all the numbers together, and all the variables
-2.5x+1=0
We move all terms containing x to the left, all other terms to the right
-2.5x=-1
x=-1/-2.5
x=1/2.5
| (x-3)^2=187 | | x^2-32x+2565=0 | | S=50-(0.9d) | | -4n+8n=8 | | 36+k=36 | | 10(1.375)^13t=30 | | 5(n)=0.5n+12.5 | | 8-3(c+2=-13 | | 23x-12=133 | | 6=3x=x-8 | | x-68=-3x | | 88+v=105 | | 4x+0.5=1.5 | | 3(4-2x)=6(-x+2) | | x-68=-x3 | | 84+(x+58)+(x+11)=180 | | 4a-5=3a-5 | | 70x=-15(x-2) | | 3x-4=2x-2+x | | 3x-8-x=42 | | (2x+12)+x+30=180 | | 4(c+7)=9(c-1)+22 | | 4(x-3)=1/2(x/2+5) | | 5x-2(1/3x-7/3)=22 | | 41/2x+3=3x+12-x | | 90=-4.959+3.496x | | 91=13*n | | h+23=41 | | 2x+13=(3x) | | -26c+52=-390 | | -7+12=9s | | 2x^2-4=x^2+20 |